Subcycle transfer of photon momentum in nondipole tunneling ionization. Issue 7 (January 2020) - Ni, H; Donsa, S; Burgdörfer, J
Synopsis: We study the subcycle transfer of photon momentum in tunneling ionization beyond the dipole approximation using the attoclock setup. We separate the momentum transfer during tunneling and propagation in continuum using the backpropagation method.